One World or None : Albert Schweitzer as a Peace Activist - Zagorac, Ivana (2012)
The paper analyses the role of Albert Schweitzer in the antinuclear movement during the 1950s and 1960s. Having come face to face with the unthinkable threat of nuclear destruction, Schweitzer joins with renowned scientists to raise public awareness about the necessity of banning nuclear testing. Schweitzer applies the view summed up in the concept of reverence for life to a question of global importance, insisting on the personal responsibility of each individual for the present and future generations. His contribution to the antinuclear movement also sheds light on the decisive role of the movement in the formation of the field of bioethics. In conclusion, the authoress points to the need for redefining the origins of bioethics.
Projekt MZOS
ENG